Prospecting CCS Project in Indonesia: A Case Study in Meratus Mountains, South Borneo - Irzon, Ronaldo; Hanang Samodra; Sam Permanadewi (Pusat Survei Geologi, 2024)
Long-term extensive carbon dioxide exposure inflicts diseases for humans and endangers the ecosystem. Carbon Capture and Storage (CCS) is a breakthrough to reduce CO2 in the atmosphere. The purpose of this study is to describe the CCS principles and suitability of this work in Indonesia, especially in the Meratus Mountains. The studied region is the major area of the Meratus Geopark. Selected ultramafic rocks from the Meratus Geopark were analyzed using X-Ray Fluorescence in the University of Tasmania. CCS project should consider the minimum implication for conservation strategy of geopark. Geologically, CCS is adapted through direct sequestration and carbon mineralization. Mafic-ultramafic lithologies are the best option for mineral carbonation. Most of the basaltic rocks in Indonesia are situated near active volcanoes that are heavily risky for CCS works. Ultramafic in the range of Meratus Geopark is clearly suitable for CCS because of its large expanse, far away from active volcanoes, without significant nickel mining activity. The project would promote geohazards and climate change issues of Meratus Geopark. In-situ CSS mineral carbonation should be located avoiding the Sultan Adam Mandiangin Serpentinite Geosite to nourish the geoconservation of Meratus Geopark. A successful CCS adaptation would be good evidence for the Indonesian government implementing the Paris Agreement. Keywords: Carbon Capture and Storage, In-situ mineral carbonation, ultramafic, Meratus Geopark.